2021
DOI: 10.3389/fpsyg.2020.464774
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Middle: How and When Psychological Contract Breach by Subordinates Relates to Weekly Emotional Exhaustion of Supervisors

Abstract: In psychological contract research, the side of the supervisor is strongly underexposed. However, supervisors are responsible for maintaining relationships with both their subordinates and senior management and are likely to be influenced by events unfolding in these relationships. In this study, we state that supervisor well-being may be affected by subordinates who fail to meet their obligations. This study adds to psychological contract research by developing an understanding of how and when subordinate psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 98 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…When employees are assured that their employers have broken the agreed-upon promises, they will be emotionally exhausted, and they will feel that there is not sufficient mental energy or work ability to be provided in their firms. This result is consistent with the findings of previous studies (e.g., De Jong et al, 2021;Gakovic and Tetrick, 2003;Maslach et al, 2001;Reimann and Guzy, 2017) elucidating that employees' emotional exhaustion can be substantially raised by their perception of PCB.…”
Section: Discussion Of Findingssupporting
confidence: 93%
See 2 more Smart Citations
“…When employees are assured that their employers have broken the agreed-upon promises, they will be emotionally exhausted, and they will feel that there is not sufficient mental energy or work ability to be provided in their firms. This result is consistent with the findings of previous studies (e.g., De Jong et al, 2021;Gakovic and Tetrick, 2003;Maslach et al, 2001;Reimann and Guzy, 2017) elucidating that employees' emotional exhaustion can be substantially raised by their perception of PCB.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Previous studies have also shown a significant positive association between PCB and employees' emotional exhaustion. For instance, De Jong et al (2021) found a substantial positive association between subordinate PCB and supervisor emotional exhaustion through a "weekly diary" survey among Dutch supervisors.…”
Section: Psychological Contract Breach and Work Alienationmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research has been done from the perspective of employers/breachers, nor has research examined the effects on them. There are a few exceptions, such as Hallier and James (1997), who examined how middle managers balanced the demands of upper management and employees; Guest and Conway (2002), who asked managers about communication and the PC; and Nadin and Williams (2012) and de Jong et al (2021), who examined how employee-initiated PC breeches impact supervisors.…”
mentioning
confidence: 99%
“…These effects can include employee deviance (Peng et al., 2016), lowered organizational citizenship behaviours (OCBs) and commitment (Coyle‐Shapiro & Kessler, 2000), lowered job satisfaction, reduced in‐role performance, and increased turnover intention and turnover (Zhao et al., 2007). Research in this area has focused on breaches from the perspective of employees, even though there have long been calls for non‐employee perspectives (de Jong et al., 2021; Guest & Conway, 2002; Hallier & James, 1997; Nadin & Williams, 2012). Little research has been done from the perspective of employers/breachers, nor has research examined the effects on them.…”
mentioning
confidence: 99%